Effect of different types and concentrations of emulsifier on the characteristics of kappa-carrageenan films - Zainal Abedin, Nur Hanani; Abu Bakar, Aelma Husna (Elsevier, 2018)
κ-Carrageenan films derived from Euchema cottoni containing different types and concentrations of emulsifier were developed. Film formation without the addition of emulsifier was used as a control. The physical, mechanical, optical and microstructural properties of these films were determined. Different types of emulsifiers (Tween 20, Tween 40 and Tween 80) exerted significant effects (P ≤ 0.05) on the thickness, moisture content and opacity of the films. Additionally, Tween 20 and Tween 40 with concentrations from 0.1 to 0.5% (v/v) significantly (P ≤ 0.05) improved the tensile strength of the films, ranging from 7.35 to 13.83 MPa. The water vapor permeability of the carrageenan films was significantly (P ≤ 0.05) affected by both factors. Increasing the emulsifier concentration also caused an increment in the number of lipid droplets contributing to a smooth surface. Therefore, this study suggests that different types and concentrations of emulsifiers play essential roles in determining the physical properties of carrageenan films.